ANALISIS DAMPAK SOSIAL EKONOMI PEMBANGUNAN BREAKWATER PADA KOMUNITAS PESISIR DI PELABUHAN PERIKANAN BEBA, TAKALAR, SULAWESI SELATAN - M Irham Ilyas; Andi Tenri Fada; Kasri Kasri; Sitti Fakhriyyah (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
Breakwater construction in coastal areas is essential for enhancing port stability and ensuring the safety of fisheries activities; however, the construction phase often generates socio-economic pressures on communities dependent on port operations. This study aims to analyze the impacts of breakwater development at Beba Fishing Port, Takalar District, with a focus on changes in fishermen’s income, local economic dynamics, and social disturbances during construction. The research employs a mixed-methods approach with an explanatory sequential design, which integrates quantitative and qualitative analyses in a sequential manner. The initial phase involved a survey of 40 respondents—including fishermen, fish traders, small-scale entrepreneurs, and nearby residents—followed by in-depth interviews and field observations based on Participatory Action Research. Chi-square analysis was used to assess the relationship between demographic characteristics and levels of impact. The findings indicate that fishermen’s income decreased by 11% during construction due to operational disruptions at the port but increased by 6% after the breakwater became fully functional. Economic impacts were more pronounced among fishermen and fish traders (χ² = 8.0; p < 0.05). Socially, communities experienced conflict, pollution, and environmental discomfort, particularly in areas affected by heavy-equipment traffic. Inferential analysis revealed significant associations between age (χ² = 11.73; p < 0.01) and education level (χ² = 8.10; p < 0.05) and conflict experiences, with younger and less-educated groups being the most affected.